The socioeconomic development of rural municipalities representing various demographic and functional types - Kudełko, Joanna (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Rural areas are usually characterised by a slower pace of growth as compared with urban areas. However, they do not constitute a uniform group of entities, representing a considerable diversity in terms of development. Among the determinants of the socio-economic development of rural areas, an important role is played by their demographic potential and the economic functions performed. The demographic typology of municipalities is used in identifying population development types in the analysed entities, depending on natural growth rates and a migration balance. The functional typology of rural municipalities is based on differences between them in terms of socio-economic structure. Understanding the relationship between the development of a municipality and its demographic and functional type is indispensable for planning the development policy and for formulating local strategies. Aim: The aim of the paper is to assess gaps in the level of development of the rural municipalities of Małopolska Voivodeship, depending on the demographic types they represent and the economic functions they perform. Results: The results of the conducted analyses indicate that the highest levels of development among Małopolska’s rural municipalities are recorded by urbanised areas. These levels are much higher than in the remaining entities classified as multi-income, agricultural and tourist municipalities. It was proved that the best developed municipalities record an increase in the number of population resulting from a positive migration rate. There is a correlation between a demographic and functional type of municipalities.